A Meta-Analysis of the Effect of Parental Involvement on Students’ Academic Achievement - Cahit Erdem (Commonwealth of Learning, 2020)
This study aims to examine the effect of parental involvement on students’ academic achievement at pre-school, elementary and secondary levels by using the meta-analysis method with respect to home-based and school-based parental involvement strategies. Data consisted of 55 independent research studies in English published between 2010 and 2019, and accessed through ERIC, Academic Search Complete, Science Direct, Wiley Online Library, and PsycNet databases. Findings revealed that the effect of parental involvement on academic achievement was positive but small. Parental expectations had the biggest effect on academic achievement and parental control had a negative and small effect. The mean effect of parental involvement on students’ academic achievement does not differ significantly according to moderator variables of education level, measurement type or measurement area but differs by developmental level of the country. The results are discussed using available related meta-analysis studies in the literature.